The Influence Of Regional Expenditures, Investment, Unemployment And Poverty Levels On Economic Growth In Regencies/Cities Of North Sumatra Province - Reza Sebayang, Ari; Erlina, Erlina; Rujiman, Rujiman (Publisher Cv. Inara, 2022)
The purpose of this study is to: 1) Analyze the effect of regional spending on economic growth in the Regency/City of North Sumatra Province whether it has a significant positive effect partially. 2) Analyzing the effect of investment on the economic growth of the Regency/City of North Sumatra Province whether it has a significant positive effect partially. And 3) Analyzing the effect of unemployment on the economic growth of the Regency/City of North Sumatra Province whether it has a significant negative effect partially. The method used is the panel data regression method. The results in this study are that Regional Expenditures have a positive and significant effect on the economic growth of districts/cities of North Sumatra Province; Investment has a positive and insignificant effect on the economic growth of districts/cities of North Sumatra Province; Unemployment and poverty rates have a negative and insignificant effect on the economic growth of districts/cities of North Sumatra Province; and Regional spending, investment, unemployment and poverty levels simultaneously have a significant effect on the economic growth of districts/cities of North Sumatra Province.